PERBANDINGAN METODE GEOGRAPHICALLY WEIGHTED REGRESSION (GWR) DAN ORDINARY LEAST SQUARE (OLS) DALAM PEMODELAN KETIMPANGAN DI PROVINSI JAWA TENGAH - Lia Miftakhul Janah; Tiani Wahyu Utami (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
nequality is a state where there is an imbalance between each other. Inequality indicates the unevenness of development that runs in an area.In Central Java, the problem of inequality among people still exists in daily life. Geographically Weight Regression method is a method that yields model parameter estimators that have localized properties at each point or location. While OrdinaryLeast Square method is a linear regression that doesn’t have territorial element. In this study aims to modeling the inequality problem that occurred in Central Java using Geographically Weight Regression method that has the nature of localization at the point and Ordinary Least Square method. Data taken from Central Statistics Agency (BPS) 2015. Through Geographically Weight Regression method can be concluded that 2 variables effect on imbalance with α 10% is variable of Total population (0,4078) and Labor (0,9502) . While the influential OLSmethod is the Human DevelopmentIndex and Averageper-capita expendixture.  AIC value of GWRis smaller than OLS Method (93.45184<105.1492)Which is mean GWR methodbetter than OlS in modelling inequality at Central Java.Keywords: Inequality, GWR,OLS